Durability of immune responses to the BNT162b2 mRNA vaccine - Suthar, Mehul; Arunachalam, Prabhu S; Hu, Mengyun; Reis, Noah; Trisal, Meera; Raeber, Olivia; Chinthrajah, Sharon; Davis-Gardner, Meredith E; Manning, Kelly; Mudvari, Prakriti; Godbole, Sucheta; Boritz, Eli; et al. (bioRxiv, 2021)
The development of the highly efficacious mRNA vaccines in less than a year since the emergence of SARS-CoV-2 represents a landmark in vaccinology. However, reports of waning vaccine efficacy, coupled with the emergence of variants of concern that are resistant to antibody neutralization, have raised concerns about the potential lack of durability of immunity to vaccination. We recently reported findings from a comprehensive analysis of innate and adaptive immune responses in 56 healthy volunteers who received two doses of the BNT162b2 vaccination. Here, we analyzed antibody responses to the homologous Wu strain as well as several variants of concern, including the emerging Mu (B.1.621) variant, and T cell responses in a subset of these volunteers at six months (day 210 post-primary vaccination) after the second dose. Our data demonstrate a substantial waning of antibody responses and T cell immunity to SARS-CoV-2 and its variants, at 6 months following the second immunization with the BNT162b2 vaccine. Notably, a significant proportion of vaccinees have neutralizing titers below the detection limit, and suggest a 3rd booster immunization might be warranted to enhance the antibody titers and T cell responses. Competing Interest Statement The authors have declared no competing interest.